causes bacterial meningitis with hearing loss in patients without direct exposure to pigs in a regional pork industry territory - Joong-Goo Kim; Gil Myeong Seong; Young Ree Kim; Sang Taek Heo; Jeong Rae Yoo (Journal of Medicine and Life Science, 2023)
Streptococcus suis (S. suis) is an emerging zoonotic pathogen that causes bacterial meningitis in humans. S. suis is an encapsulated gram-positive facultative anaerobic bacterium and is an important pathogen in pigs. This infectious disease usually manifests in humans as meningitis, endocarditis, septicemia, and arthritis. Most cases originate in Southeast Asia, and human S. suis infections are often reported in countries with a high density of pigs. Meningitis is a common clinical manifestation of S. suis infection. Moreover, hearing loss is a common complication that can be bilateral, profound, and/or permanent. This report presents two cases of bacterial meningitis and hearing loss caused by S. suis in patients without a history of direct exposure to pigs in an intensive pork industry region.